MODAL SOSIAL PEDAGANG LOPEK BUGI DESA PALUNG RAYA KECAMATAN TAMBANG KABUPATEN KAMPAR - Yati, Nur Fitri Yati; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Lopek Bugi is one type of wet cake whose basic ingredients are made from flour and grated coconut, then processed after wards wrapped using banana leaves. This one wet cake has long been known by the person who crossed the road precisely in Palung Raya Village, Tambang District. The purpose and objective of this study was to find out the elements of social capital contained in Lopek Bugi's trading business by using a descriptive leather approach and the selection of informants who were carried out using purposive sampling technique, namely the acquisition of data from informants based on criteria or certain limitations. These criteria or limitations are traders who are long-time in selling and producing Lopek Bugi at the kiosk and have employees. The data collection techniques used in this study are observation, interview, and documentation techniques. The conclusions of the results of this study stated that the elements of social capital contained in the Lopek Bugi cake trading business consisted of three components, namely social networks, beliefs and norms in which the three elements are mutually binding and need each other related to each other, in the presence of elements the element of social capital established in Lopek Bugi's trading business is able to provide comfort to every trader and is able to maintain the existence of a trading business that has been developed until now and the form of competition that occurs between traders is fair competition. Keywords: Social Capital, Lopek Bugi